2016
DOI: 10.1109/tuffc.2016.2614652
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Performance of Different Multiline Transmit Setups for Fast Volumetric Cardiac Ultrasound

Abstract: It was previously demonstrated in 2-D echocardiography that a proper multiline transmit (MLT) implementation can be used to increase frame rate while preserving image quality. Initial findings for extending MLT to 3-D showed that it might address the low spatiotemporal resolution of current volumetric ultrasound systems. However, to date, it remains unclear how much transmit/receive parallelization would be possible using a 3-D MLT system. Therefore, the aim of this paper was to contrast different MLT setups f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Such staggering was chosen to be half the thickness of the hollow cone at the focal depth. The cross-talk energy level of the MLT systems can be determined using the process described in [17]. As such, simulations of the two-way beam profiles were performed on a plane parallel to the transducer surface (i.e., C-plane) at a depth of 65 mm (i.e., around halfway the common imaging depth for cardiac applications).…”
Section: Parallelized Scan Sequencementioning
confidence: 99%
See 4 more Smart Citations
“…Such staggering was chosen to be half the thickness of the hollow cone at the focal depth. The cross-talk energy level of the MLT systems can be determined using the process described in [17]. As such, simulations of the two-way beam profiles were performed on a plane parallel to the transducer surface (i.e., C-plane) at a depth of 65 mm (i.e., around halfway the common imaging depth for cardiac applications).…”
Section: Parallelized Scan Sequencementioning
confidence: 99%
“…As such, simulations of the two-way beam profiles were performed on a plane parallel to the transducer surface (i.e., C-plane) at a depth of 65 mm (i.e., around halfway the common imaging depth for cardiac applications). This depth was chosen based on our previous in silico findings [17] while using the exact same system configuration. It was shown that the best performing system at this depth was also the system of choice at other depths and steering angles.…”
Section: Parallelized Scan Sequencementioning
confidence: 99%
See 3 more Smart Citations